2018
DOI: 10.1159/000492571
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Endurance Exercise and Diet on Atherosclerosis in Young and Aged ApoE<sup>–/–</sup> and Wild-Type Mice

Abstract: Background: Atherosclerosis is the leading cause of death worldwide. The disease development is by and large driven by old age and lifestyle factors, such as diet, physical activity, and smoking. In the present study, we have investigated the effect of exercise and diet on the development of atherosclerosis in young and aged mice. Objective: This study aimed at comparing multiple age-dependent factors that may influence atherosclerosis in a transgenic mouse model. Methods: Young (14 weeks) and aged (49–52 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
1
11
2
Order By: Relevance
“…ApoE deficient (apoE -/-) mice can spontaneously develop atherosclerosis which stimulate atherosclerotic pathological processes in the arteries of humans with lesions that can be observed during the development of atherosclerosis (Nakashima et al, 1994). Furthermore, aged apoE -/mice (20 to 40 weeks of age) developed more advanced, fibrous plaques, with abundant fibrous tissue and larger necrotic cores (Jakic et al, 2019). To observe the effect of aging on more severe atherosclerosis lesions, we compared the plaque areas in young (5-week) and old (32-week) apoE -/mice with the intervention of a high fat diet for 32 weeks, another risk factor for AS, to ensure the formation of complex plaques (Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…ApoE deficient (apoE -/-) mice can spontaneously develop atherosclerosis which stimulate atherosclerotic pathological processes in the arteries of humans with lesions that can be observed during the development of atherosclerosis (Nakashima et al, 1994). Furthermore, aged apoE -/mice (20 to 40 weeks of age) developed more advanced, fibrous plaques, with abundant fibrous tissue and larger necrotic cores (Jakic et al, 2019). To observe the effect of aging on more severe atherosclerosis lesions, we compared the plaque areas in young (5-week) and old (32-week) apoE -/mice with the intervention of a high fat diet for 32 weeks, another risk factor for AS, to ensure the formation of complex plaques (Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that forced treadmill walking, but not voluntary wheel running or forced swimming, prevented early atherosclerosis progression. A significant reduction in aortic lesion size has been recently reported in young ApoE −/− mice (without LEAD) after 5 weeks of a treadmill endurance program 39 . Our data emphasizes the clinical relevance of endurance treadmill ET for reducing cardiovascular mortality in LEAD patients as previously reported 40 .…”
Section: Discussionmentioning
confidence: 84%
“…Exercise promotes cardiovascular health and reduces atherosclerotic lesion size and vulnerability. In both ApoE knockout and LDL receptor knockouts fed a western style diet, aerobic exercise training reduced early lesion size formation and enhanced lesion regression (59, 60). Moreover, exercise training in diabetic ApoE knockout animals resulted in improved glucose tolerance, lesion size, and plaque stability.…”
Section: Role Of Innate Immunity In Cardiovascular Diseasementioning
confidence: 99%